Borrowing Agreement with the Central Bank of Malta. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
In light of the multilateral effort to ensure the adequacy of the financial resources available to the International Monetary Fund, and with a view to supporting the Fund's ability to provide timely and effective balance of payments assistance to its members, the Central Bank of Malta agrees to lend to the Fund an SDR denominated amount up to the equivalent of EUR120 million, on the terms and conditions set in this policy paper.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet